Problems of social exclusion – the context of child poverty prevention - Kawczyńska-Butrym, Zofia (Problemy społeczne: Trwałość i zmienność w dynamicznej rzeczywistości. Księga jubileuszowa z okazji 45-lecia pracy naukowej i dydaktycznej Profesor Jolanty Grotowskiej-Leder, 2022)
Social exclusion is a social issue coexisting with poverty and arising as a result of deficits, limited opportunities and resources of individuals, families or social groups. The importance of human capital in overcoming exclusion and the goals adopted in the European Union countries in the Europe 2020 Strategy were referred. Child poverty turned out to be a burning issue in all EU States. The Polish solution of the child poverty is Rodzina 500+ [Family 500+] program addressed to families with dependent children aged 0–17. The chapter presents the data of Central Statistics Office covering the years of the program functioning which show a reduction in extreme poverty in families with children, as well as opinions of CBOS respondents and parents benefiting from the program. Declarations and purposes of spending the money, major changes in the family situation as well as doubts about the future of the program were indicated.